1943
DOI: 10.1590/s0074-02761943000300011
|View full text |Cite
|
Sign up to set email alerts
|

Novo transmissor silvestre do "Trypanosoma (Schizotrypanum) cruzi" (Chagas, 1909)

Abstract: In nests of opossum (Didelphis aurita), localized in palm-trees of the species Attalea indaya Dr., the authors found a new tritatoma, the description of which is being made by Dr. H. LENT. They verified that this triatoma had been naturally infected by Trypanosoma (Schizotrhypanum) cruzy. Two guinea-pigs were subsequently infected by peritoneal inoculation of excrements of this new triatoma. The xenodiagnosis of these guinea-pigs, made with normal nymphas of. T. megistus and T. infesta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

1980
1980
2000
2000

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…Studies on T. cruzi infection in Didelphis sp. in different regions of Brazil revealed infection rates varying from 20.6% to 37.9% (Guimarães & Jansen 1943, Miles 1976, Mello 1982, Fernandes et al 1991. In the present work T. cruzi infection rates of 21.9% and 45.2% were found in D. marsupialis captured in the Santa Catarina and Arvoredo Islands, respectively.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Studies on T. cruzi infection in Didelphis sp. in different regions of Brazil revealed infection rates varying from 20.6% to 37.9% (Guimarães & Jansen 1943, Miles 1976, Mello 1982, Fernandes et al 1991. In the present work T. cruzi infection rates of 21.9% and 45.2% were found in D. marsupialis captured in the Santa Catarina and Arvoredo Islands, respectively.…”
Section: Discussionsupporting
confidence: 52%
“…Previous studies revealed distinct infection rates of Didelphis sp. by T. cruzi in different regions of Brazil such as 35.7% in Rio de Janeiro (Guimarães & Jansen 1943), 24% in the Amazon basin (Miles 1976), 20.6% in Mambaí, State of Goiás (Mello 1982) and 37.9% in Bambuí, State of Minas Gerais (Fernandes et al 1991).…”
mentioning
confidence: 99%
“…The first case of natural infection by T. cruzi in marsupials was reported by Robertson (1929) in D. marsupialis. Further studies have confirmed the importance of this reservoir showing levels of natural infection ranging from 17 to 100% (Rodrigues & Mello 1942, Guimarães & Jansen 1943, McKeever & Gorman 1958, Herrera & Urdaneta-Morales 1992, Travi et al 1994.…”
mentioning
confidence: 85%